Optical fiber coating adhesion promoter as well as preparation method and application thereof
By adding modified epoxy resin and modified filler to the adhesion promoter of optical fiber coating, the problems of poor compatibility, instability and unsatisfactory peeling rate in the prior art are solved, and higher adhesion and reliability of optical fiber coatings are achieved.
Patent Information
- Application Number
- CN202411943636.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing fiber optic coating adhesion promoters have problems such as poor compatibility, unstable and easy hydrolysis, and unsatisfactory peeling rate, which affects the service life and market competitiveness of the fiber.
By adding modified epoxy resin and modified filler to the fiber coating adhesion promoter, a more stable cross-linking network and a more uniform coating are formed, improving the long-term reliability of the coating and peeling pass rate.
The adhesion between the optical fiber and the coating is improved, the reliability and stripping pass rate of the optical fiber are improved, and the integrity and optical performance of the optical fiber are maintained.
Smart Images

Figure BDA0005214916210000121 
Figure BDA0005214916210000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to an optical fiber coating adhesion promoter and a preparation method and application thereof. Background Art
[0002] Optical fiber coating is a material specially designed for coating the surface of optical fiber. Its main purpose is to protect the optical fiber from physical damage, environmental factors (such as humidity, temperature changes), and maintain the optical properties of the optical fiber. Optical fiber coating usually consists of two layers: primary coating and secondary coating. The primary coating is directly applied to the exposed optical fiber surface, and the thickness is usually around a few microns. Its main functions are: providing buffering and elasticity, absorbing external impact, and preventing the optical fiber from bending or breaking. Reduce the microbending loss of the optical fiber and maintain the high efficiency of signal transmission. Prevent moisture penetration and avoid the degradation of optical fiber performance over time. The secondary coating is a harder coating applied on top of the primary coating, and the thickness can reach tens of microns. Its main functions are: providing additional mechanical protection and enhancing the wear and scratch resistance of the optical fiber. It facilitates the handling of optical fiber during wiring and installation, such as perforation, bending, etc. Sometimes it also plays the role of color identification to facilitate the identification of different types of optical fibers.
[0003] Optical fiber coatings prepared with acrylic resin formula systems are used for primary coating, and mainly use physical forces such as hydrogen bonds to form forces with optical fibers, thereby coating the optical fiber surface. However, the forces formed by hydrogen bonds are weak, and during the use of optical fibers, the coating may fall off, affecting the service life of the optical fiber. Therefore, it is usually necessary to add adhesion promoters to optical fiber coatings.
[0004] Conventional optical fiber coating adhesion promoters, such as silane coupling agents such as KH550 and KH560, have problems such as poor compatibility, instability and easy hydrolysis, and are also prone to local aggregation, resulting in excessive local adhesion of the coating, and the coating cannot be stripped cleanly. Chinese patent 202211057564.X provides an optical fiber coating adhesion promoter and a preparation method thereof. By adding a small amount of adhesion promoter, the adhesion between the optical fiber and the coating can be improved, and the reliability of the optical fiber can be improved. However, the long-term reliability and stripping pass rate are poor, which seriously affects the use effect and its market competitiveness.
[0005] Therefore, there is an urgent need for an optical fiber coating adhesion promoter with good adhesion promotion effect and reliability. Summary of the invention
[0006] The purpose of the present invention is to provide an optical fiber coating adhesion promoter and a preparation method and application thereof, which can improve the adhesion between the optical fiber and the coating and enhance the reliability of the optical fiber.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] An optical fiber coating adhesion promoter, comprising the following components in parts by mass: 20-25 parts of modified epoxy resin, 4-7 parts of epoxy acrylate, 12-16 parts of modified filler, 32-38 parts of propylene glycol methyl ether acetate, 13-18 parts of isobutyl alcohol, 6-10 parts of phosphoric acid and 5-7 parts of water;
[0009] The preparation method of modified epoxy resin is:
[0010] (1) In a nitrogen environment, 700-710 parts by weight of epoxy resin is heated to 135-140° C., and then 0.7-0.9 parts by weight of N,N-dimethylbenzylamine is added, and the mixture is kept at this temperature for 8-10 hours to obtain a polyepoxide;
[0011] (2) 35-38 parts by weight of N-methylethanolamine and 220-230 parts by weight of amino-terminated liquid nitrile rubber are added to the polyepoxide compound in sequence, reacted at 125-130° C. for 6-8 hours, and then cooled to room temperature to obtain a modified epoxy resin.
[0012] Furthermore, the epoxy resin is selected from one or more of epoxy resin A, epoxy resin B, and epoxy resin C. The epoxy equivalent of epoxy resin A is 179-189 g / Eq; the epoxy equivalent of epoxy resin B is 167-175 g / Eq, and the epoxy equivalent of epoxy resin C is 400-455 g / Eq.
[0013] Furthermore, the epoxy resin is a compound of epoxy resin A, epoxy resin B, and epoxy resin C in a mass ratio of 1: (0.5-0.7): (1.3-1.5), and the epoxy equivalent of epoxy resin A is 179-189 g / Eq (brand: Huntsman, model GY764); the epoxy equivalent of epoxy resin B is 167-175g / Eq (brand: Huntsman, model GY289), epoxy resin C has an epoxy equivalent of 400-455g / Eq (brand: Huntsman, model GY298).
[0014] Adding epoxy resin and epoxy acrylate to the optical fiber coating adhesion promoter can improve the tensile strength of the optical fiber coating prepared by the acrylate resin formula system, but the optical fiber coating adhesion promoter has an unsatisfactory effect on the long-term reliability of the coating. The fiber optic coating adhesion promoter prepared by modifying the epoxy resin compounded with PZ756-1 / 67 epoxy resin and Hansen Epikote834 liquid bisphenol A epoxy resin can improve the long-term reliability of the coating. The modified epoxy resin can form a more stable cross-linked network by introducing N-methylethanolamine and amino-terminated liquid nitrile rubber, which is not easy to degrade and enhances the thermal stability of the resin, thereby maintaining the integrity and optical properties of the fiber optic coating. However, under this condition, the fiber optic coating adhesion promoter is added to the coating, and the stripping pass rate is not ideal.
[0015] Furthermore, the preparation method of the modified filler is:
[0016] (1) mixing carboxylated double-walled carbon nanotubes, carboxylated graphene oxide and carboxylated silicon dioxide in a mass ratio of 1: (1.2-1.5): (0.4-0.7) to obtain a filler, mixing 1 mass part of 3-isocyanate propyltrimethoxysilane and 0.12-0.15 mass parts of the filler under a nitrogen atmosphere, performing ultrasonic treatment for 20-25 minutes, adding 50-55 mass parts of N,N-dimethylformamide, stirring at 100-108° C. for 2-3 hours, centrifuging, and freeze-drying the obtained solid product A to obtain an isocyanate-modified filler;
[0017] (2) 9-12 parts by weight of isocyanate-modified filler and 60-65 parts by weight of ethanol are mixed, and then an aqueous solution of carboxylated polystyrene microspheres is added dropwise, stirred at 55-60° C. for 2-3 hours, centrifuged, and the obtained solid product B is freeze-dried to obtain a modified filler.
[0018] Furthermore, the average particle size of the carboxylated polystyrene microspheres in the carboxylated polystyrene microsphere aqueous solution is 20 nm, and the solid content is 2.5 wt %. It is purchased from Xianfeng Nano, item number: 103392. Furthermore, the mass ratio of the isocyanate modified filler to the carboxylated polystyrene microspheres is 10:2-5.
[0019] Furthermore, the carboxylated double-walled carbon nanotubes have a diameter of 2-4 nm, a length of 0.5-2 μm, and a carboxyl content of 2.58 wt %, and are purchased from Xianfeng Nano, item number: 100227.
[0020] Furthermore, the carboxylated graphene oxide sheet has a diameter of 0.5-5 micrometers and a thickness of 0.8-1.2 nm, and is purchased from Xianfeng Nano, item number: 100009.
[0021] Furthermore, the average size of carboxylated silica is 20 nm and is purchased from Xianfeng Nano, item number: 103113.
[0022] The present invention can improve the stripping qualification rate of the coating by adding modified fillers to the optical fiber coating adhesion promoter. The fillers can achieve better dispersion in the epoxy resin matrix through surface modification, and can avoid aggregation and agglomeration in the coating, thereby forming a more uniform coating and reducing defects on the optical fiber surface. Modification with carboxylated polystyrene microspheres can improve the compatibility of system components and improve the stability of the optical fiber coating adhesion promoter.
[0023] Furthermore, the epoxy acrylate is selected from one or more of CN104NS, CN120NS, CN150NS, and CN2003NS. Purchased from brand: Sartomer.
[0024] In order to improve the elongation at break, the epoxy acrylate is further mixed with CN104NS, CN150NS and CN2003NS in a mass ratio of 1: (1.4-1.6): (0.2-0.5).
[0025] The present invention also provides a method for preparing an adhesion promoter for optical fiber coatings, the method comprising the following steps: mixing propylene glycol methyl ether acetate, isobutyl alcohol and water, adding epoxy resin, modified filler and epoxy acrylate in sequence under stirring, adding dropwise phosphoric acid after stirring evenly, and continuing stirring for 2-3 hours to obtain the product.
[0026] The present invention also provides the application of the optical fiber coating adhesion promoter for preparing the optical fiber coating prepared by the acrylic resin formula system.
[0027] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0028] 1. Adding modified epoxy resin and epoxy acrylate to the optical fiber coating adhesion promoter of the present invention can improve the tensile strength of the optical fiber coating prepared from the acrylate resin formula system.
[0029] 2. The present invention is to treat waterborne epoxy resin EP137, Huntsman The fiber optic coating adhesion promoter prepared by modifying the epoxy resin compounded with PZ756-1 / 67 epoxy resin and Hansen Epikote834 liquid bisphenol A epoxy resin can improve the long-term reliability of the coating.
[0030] 3. The present invention can improve the stripping qualification rate of the coating by adding modified fillers to the optical fiber coating adhesion promoter. Modification with carboxylated polystyrene microspheres can improve the compatibility of system components and the stability of the optical fiber coating adhesion promoter. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] This embodiment provides an optical fiber coating adhesion promoter, comprising the following components in parts by mass: 22 parts of modified epoxy resin, 6 parts of epoxy acrylate, 14 parts of modified filler, 36 parts of propylene glycol methyl ether acetate, 15 parts of isobutyl alcohol, 8 parts of phosphoric acid and 6 parts of water;
[0034] The preparation method of modified epoxy resin is:
[0035] (1) In a nitrogen environment, 705 parts by weight of epoxy resin was heated to 138° C., and then 0.8 parts by weight of N,N-dimethylbenzylamine was added, and the mixture was kept at this temperature for 9 hours to obtain a polyepoxide;
[0036] (2) 37 parts by mass of N-methylethanolamine and 225 parts of amino-terminated liquid nitrile rubber were added to the polyepoxy compound in sequence, and the mixture was reacted at 127° C. for 7 hours and then cooled to room temperature to obtain a modified epoxy resin.
[0037] Amino-terminated liquid nitrile rubber was purchased from Jining Fangyu Chemical Co., Ltd., with an average molecular weight of 10,000 Da.
[0038] The epoxy resin is a compound of epoxy resin A, epoxy resin B and epoxy resin C in a mass ratio of 1:0.6:1.4, and the epoxy equivalent of epoxy resin A is 179-189g / Eq (product brand: Huntsman, model GY764); the epoxy equivalent of epoxy resin B is 167-175g / Eq (product brand: Huntsman, model GY289), epoxy resin C has an epoxy equivalent of 400-455g / Eq (product brand: Huntsman, model GY298).
[0039] The preparation method of the modified filler is:
[0040] (1) Carboxylated double-walled carbon nanotubes, carboxylated graphene oxide and carboxylated silica in a mass ratio of 1:1.4:0.6 were mixed to obtain a filler, and 1 mass part of 3-isocyanate propyltrimethoxysilane and 0.14 mass part of the filler were mixed under a nitrogen atmosphere, and ultrasonicated for 22 minutes, and 52 mass parts of N,N-dimethylformamide were added, and stirred at 105° C. for 2.5 hours, and centrifuged to obtain a solid product A, and freeze-dried to obtain an isocyanate-modified filler;
[0041] (2) 10 parts by mass of the isocyanate-modified filler and 62 parts by mass of ethanol were mixed, and then an aqueous solution of carboxylated polystyrene microspheres was added dropwise, stirred at 57° C. for 2.5 h, and centrifuged to obtain a solid product B, which was freeze-dried to obtain a modified filler.
[0042] The average particle size of the carboxylated polystyrene microspheres in the carboxylated polystyrene microsphere aqueous solution is 20 nm, and the solid content is 2.5 wt %. The solution was purchased from Xianfeng Nano, item number: 103392.
[0043] The mass ratio of the isocyanate-modified filler to the carboxylated polystyrene microspheres is 10:3.
[0044] The carboxylated double-walled carbon nanotubes have a diameter of 2-4 nm, a length of 0.5-2 μm, and a carboxyl content of 2.58 wt %. They were purchased from Xianfeng Nano, item number: 100227.
[0045] The carboxylated graphene oxide sheet has a diameter of 0.5-5 microns and a thickness of 0.8-1.2 nm. It was purchased from Xianfeng Nano, item number: 100009.
[0046] The average size of carboxylated silica is 20 nm and it was purchased from Xianfeng Nano, item number: 103113.
[0047] The epoxy acrylate is a mixture of CN104NS, CN150NS and CN2003NS in a mass ratio of 1:1.5:0.4.
[0048] The preparation method of the optical fiber coating adhesion promoter comprises the following steps: mixing propylene glycol methyl ether acetate, isobutyl alcohol and water, adding epoxy resin, modified filler and epoxy acrylate in sequence under stirring, adding phosphoric acid dropwise after stirring evenly, and continuing stirring for 2.5 hours to obtain the optical fiber coating adhesion promoter.
[0049] Example 2
[0050] This embodiment provides an optical fiber coating adhesion promoter, comprising the following components in parts by mass: 20 parts of modified epoxy resin, 4 parts of epoxy acrylate, 12 parts of modified filler, 32 parts of propylene glycol methyl ether acetate, 13 parts of isobutyl alcohol, 6 parts of phosphoric acid and 5 parts of water;
[0051] The preparation method of modified epoxy resin is:
[0052] (1) In a nitrogen environment, 700 parts by weight of epoxy resin was heated to 135° C., and then 0.7 parts by weight of N,N-dimethylbenzylamine was added, and the mixture was kept at this temperature for 8 hours to obtain a polyepoxide;
[0053] (2) 35 parts by mass of N-methylethanolamine and 220 parts by mass of amino-terminated liquid nitrile rubber were added to the polyepoxy compound in sequence, and the mixture was reacted at 125° C. for 6 hours and then cooled to room temperature to obtain a modified epoxy resin.
[0054] Amino-terminated liquid nitrile rubber was purchased from Jining Fangyu Chemical Co., Ltd., with an average molecular weight of 10,000 Da.
[0055] The epoxy resin is a compound of epoxy resin A, epoxy resin B and epoxy resin C in a mass ratio of 1:0.5:1.3, and the epoxy equivalent of epoxy resin A is 179-189g / Eq (product brand: Huntsman, model GY764); the epoxy equivalent of epoxy resin B is 167-175g / Eq (product brand: Huntsman, model GY289), epoxy resin C has an epoxy equivalent of 400-455g / Eq (product brand: Huntsman, model GY298).
[0056] The preparation method of the modified filler is:
[0057] (1) Under a nitrogen atmosphere, 1 part by mass of 3-isocyanate propyltrimethoxysilane and 0.12 parts by mass of filler were mixed, ultrasonicated for 20 minutes, 50 parts by mass of N,N-dimethylformamide were added, stirred at 100° C. for 2 hours, centrifuged, and the obtained solid product A was freeze-dried to obtain an isocyanate-modified filler;
[0058] (2) 10 parts by weight of isocyanate-modified filler and 60 parts by weight of ethanol were mixed, and then an aqueous solution of carboxylated polystyrene microspheres was added dropwise, stirred at 55° C. for 2 h, and centrifuged to obtain a solid product B, which was freeze-dried to obtain a modified filler.
[0059] The average particle size of the carboxylated polystyrene microspheres in the carboxylated polystyrene microsphere aqueous solution is 20 nm, and the solid content is 2.5 wt %. The solution was purchased from Xianfeng Nano, item number: 103392.
[0060] The mass ratio of the isocyanate-modified filler to the carboxylated polystyrene microspheres is 5:1.
[0061] The carboxylated double-walled carbon nanotubes have a diameter of 2-4 nm, a length of 0.5-2 μm, and a carboxyl content of 2.58 wt %. They were purchased from Xianfeng Nano, item number: 100227.
[0062] The epoxy acrylate is a mixture of CN104NS, CN150NS and CN2003NS in a mass ratio of 1:1.4:0.2.
[0063] The preparation method of the optical fiber coating adhesion promoter comprises the following steps: mixing propylene glycol methyl ether acetate, isobutyl alcohol and water, adding epoxy resin, modified filler and epoxy acrylate in sequence under stirring, adding phosphoric acid dropwise after stirring evenly, and continuing stirring for 2 hours to obtain the optical fiber coating adhesion promoter.
[0064] Example 3
[0065] This embodiment provides an optical fiber coating adhesion promoter, comprising the following components in parts by mass: 25 parts of modified epoxy resin, 7 parts of epoxy acrylate, 16 parts of modified filler, 38 parts of propylene glycol methyl ether acetate, 18 parts of isobutyl alcohol, 10 parts of phosphoric acid and 7 parts of water;
[0066] The preparation method of modified epoxy resin is:
[0067] (1) In a nitrogen environment, 710 parts by weight of epoxy resin was heated to 140° C., and then 0.9 parts by weight of N,N-dimethylbenzylamine was added, and the mixture was kept warm for 10 hours to obtain a polyepoxide;
[0068] (2) 38 parts by mass of N-methylethanolamine and 230 parts by mass of amino-terminated liquid nitrile rubber were added to the polyepoxy compound in sequence, and the mixture was reacted at 130° C. for 8 hours and then cooled to room temperature to obtain a modified epoxy resin.
[0069] Amino-terminated liquid nitrile rubber was purchased from Jining Fangyu Chemical Co., Ltd., with an average molecular weight of 10,000 Da.
[0070] The epoxy resin is a compound of epoxy resin A, epoxy resin B, and epoxy resin C in a mass ratio of 1:0.7:1.5, and the epoxy equivalent of epoxy resin A is 179-189g / Eq (product brand: Huntsman, model GY764); the epoxy equivalent of epoxy resin B is 167-175g / Eq (product brand: Huntsman, model GY289), epoxy resin C has an epoxy equivalent of 400-455g / Eq (product brand: Huntsman, model GY298).
[0071] The preparation method of the modified filler is:
[0072] (1) Under a nitrogen atmosphere, 1 part by mass of 3-isocyanate propyltrimethoxysilane and 0.15 parts by mass of filler were mixed, ultrasonicated for 25 minutes, 55 parts by mass of N,N-dimethylformamide were added, stirred at 108° C. for 3 hours, centrifuged, and the obtained solid product A was freeze-dried to obtain an isocyanate-modified filler;
[0073] (2) 10 parts by mass of the isocyanate-modified filler and 65 parts by mass of ethanol were mixed, and then an aqueous solution of carboxylated polystyrene microspheres was added dropwise, stirred at 60° C. for 3 h, and centrifuged to obtain a solid product B, which was freeze-dried to obtain a modified filler.
[0074] The average particle size of the carboxylated polystyrene microspheres in the carboxylated polystyrene microsphere aqueous solution is 20 nm, and the solid content is 2.5 wt %. The solution was purchased from Xianfeng Nano, item number: 103392.
[0075] The mass ratio of the isocyanate-modified filler to the carboxylated polystyrene microspheres is 2:1.
[0076] The carboxylated double-walled carbon nanotubes have a diameter of 2-4 nm, a length of 0.5-2 μm, and a carboxyl content of 2.58 wt %. They were purchased from Xianfeng Nano, item number: 100227.
[0077] The carboxylated graphene oxide sheet has a diameter of 0.5-5 microns and a thickness of 0.8-1.2 nm. It was purchased from Xianfeng Nano, item number: 100009.
[0078] The average size of carboxylated silica is 20 nm and it was purchased from Xianfeng Nano, item number: 103113.
[0079] The epoxy acrylate is a mixture of CN104NS, CN150NS and CN2003NS in a mass ratio of 1:1.6:0.5.
[0080] The preparation method of the optical fiber coating adhesion promoter comprises the following steps: mixing propylene glycol methyl ether acetate, isobutyl alcohol and water, adding epoxy resin, modified filler and epoxy acrylate in sequence under stirring, adding phosphoric acid dropwise after stirring evenly, and continuing stirring for 3 hours to obtain the optical fiber coating adhesion promoter.
[0081] Comparative Example 1
[0082] The difference between this comparative example and Example 1 is that this example provides an optical fiber coating adhesion promoter, including the following components in parts by mass: 15 parts of modified epoxy resin, 13 parts of epoxy acrylate, 14 parts of modified filler, 36 parts of propylene glycol methyl ether acetate, 15 parts of isobutyl alcohol, 8 parts of phosphoric acid and 6 parts of water.
[0083] Comparative Example 2
[0084] The difference between this comparative example and Example 1 is that the epoxy resin is a compound of epoxy resin A, epoxy resin B, and epoxy resin C in a mass ratio of 1:1:1, and the epoxy equivalent of epoxy resin A is 179-189 g / Eq (product brand: Huntsman, model GY764); the epoxy equivalent of epoxy resin B is 167-175g / Eq (product brand: Huntsman, model GY289), epoxy resin C has an epoxy equivalent of 400-455g / Eq (product brand: Huntsman, model GY298).
[0085] Comparative Example 3
[0086] The difference between this comparative example and Example 1 is that the epoxy resin is a compound of epoxy resin A, epoxy resin B, and epoxy resin C in a mass ratio of 1:0.6:1.4, and the epoxy equivalent of epoxy resin A is 460-630 g / mol (water-based epoxy resin EP137, purchased from Guangdong Qirun New Materials Co., Ltd.); the epoxy equivalent of epoxy resin B is 210-230 g / mol (Phoenix WSR6101 epoxy resin); the epoxy equivalent of epoxy resin C is 184-195 g / mol (Phoenix epoxy resin WSR618).
[0087] The epoxy resin is a mixture of American Hanson Epikote WD-52A, American Hanson Epikote TM 6520-WH-53A and Phoenix epoxy resin e44 in a mass ratio of 1:0.6:1.4.
[0088] Comparative Example 4
[0089] The difference between this comparative example and Example 1 is that the carboxylated polystyrene microsphere aqueous solution is replaced by a nano-titanium dioxide aqueous solution, the nano-titanium dioxide content in the nano-titanium dioxide aqueous solution is 2.5 wt %, and the average particle size of the nano-titanium dioxide is 20 nm.
[0090] Comparative Example 5
[0091] The difference between this comparative example and Example 1 is that the diameter of the carboxylated double-walled carbon nanotube is 10-20 nm, the length is 0.5-2 μm, and the carboxyl content is 2 wt%. It is purchased from Xianfeng Nano, item number: 100262. The average size of the carboxylated silicon dioxide is 100 nm. It is purchased from Xianfeng Nano, item number: 103114. The carboxylated graphene oxide is replaced by graphene oxide, the graphene oxide sheet diameter is 0.5-5 μm, the thickness is: 0.8-1.2 nm, purchased from Xianfeng Nano, item number: 100602.
[0092] Comparative Example 6
[0093] The difference between this comparative example and Example 1 is that carboxylated double-walled carbon nanotubes, carboxylated graphene oxide and carboxylated silicon dioxide are mixed in a mass ratio of 1:1:1 to obtain a filler.
[0094] Comparative Example 7
[0095] The difference between this comparative example and Example 1 is that the epoxy acrylate is a mixture of CN104NS, CN150NS and CN2003NS in a mass ratio of 1:1:1.
[0096] Performance Testing
[0097] 1. Add the optical fiber coating adhesion promoter prepared in Examples 1-3 and Comparative Examples 1-7 to the optical fiber acrylic coating in an amount of 5 wt%. Perform the following performance tests:
[0098] The tensile strength and elongation at break tests refer to GBT1040.2-2006 and GBT1040.3-2006 tests respectively.
[0099] 2. Apply the above coating as a primary coating on the surface of the optical fiber with a thickness of 5 microns, and perform the following performance tests:
[0100] Long-term reliability: Take 150m of 125μm diameter optical fiber and immerse it completely in 85℃ hot water. Measure its cladding loss every 24 hours (cladding loss less than 15dB / km is qualified), and determine the number of days to pass.
[0101] Stripping performance: Take 1 meter long 400μm diameter optical fiber and use a fiber stripping machine to strip it. 60 fibers are stripped in each group. Each group of samples is wiped three times with acetone after stripping. The stripped part is observed under a microscope to see if there is any coating residue. The stripped part is qualified if it is clean and free of residue.
[0102] 3. Storage stability: Place the optical fiber coating adhesion promoter prepared in Examples 1-3 and Comparative Examples 1-7 in a 100 mL beaker at room temperature. If any of the following phenomena such as crystallization, whitening, turbidity, or stratification occurs, the product is considered unqualified. The qualified days are counted.
[0103] Table 1 Performance test results
[0104]
[0105]
[0106] From the above performance test results, it can be seen that the optical fiber coating adhesion promoters of Examples 1-3 can improve the adhesion between the optical fiber and the coating and enhance the reliability of the optical fiber. In particular, the comprehensive performance of Example 1 is the most outstanding, which is mainly because the various components work synergistically.
[0107] However, the comparative example did not adopt the necessary technical solution, resulting in that its corresponding performance tests were significantly worse than those of the embodiment. In the comparative example, the ratio of the modified epoxy resin and epoxy acrylate was changed, and it can be seen that the overall effect decreased, proving that the modified epoxy resin and epoxy acrylate solution has an important influence on the overall effect of the optical fiber coating adhesion promoter. The modified epoxy resin solution was not used in comparative examples 2-3, and it can be seen from the results that the reliability was affected. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.
[0108] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An optical fiber coating adhesion promoter, characterized in that: The invention comprises the following components in parts by weight: 20-25 parts of modified epoxy resin, 4-7 parts of epoxy acrylate, 12-16 parts of modified filler, 32-38 parts of propylene glycol methyl ether acetate, 13-18 parts of isobutyl alcohol, 6-10 parts of phosphoric acid and 5-7 parts of water; The preparation method of modified epoxy resin is: (1) In a nitrogen environment, 700-710 parts by weight of epoxy resin is heated to 135-140° C., and then 0.7-0.9 parts by weight of N,N-dimethylbenzylamine is added, and the mixture is kept at this temperature for 8-10 hours to obtain a polyepoxide; (2) 35-38 parts by weight of N-methylethanolamine and 220-230 parts by weight of amino-terminated liquid nitrile rubber are added to the polyepoxide compound in sequence, reacted at 125-130° C. for 6-8 hours, and then cooled to room temperature to obtain a modified epoxy resin.
2. The optical fiber coating adhesion promoter according to claim 1, characterized in that: The epoxy resin is selected from one or more of epoxy resin A, epoxy resin B, and epoxy resin C. The epoxy equivalent of epoxy resin A is 179-189 g / Eq; the epoxy equivalent of epoxy resin B is 167-175 g / Eq; and the epoxy equivalent of epoxy resin C is 400-455 g / Eq.
3. The optical fiber coating adhesion promoter according to claim 2, characterized in that: The epoxy resin is a compound of epoxy resin A, epoxy resin B and epoxy resin C in a mass ratio of 1: (0.5-0.7): (1.3-1.5).
4. The optical fiber coating adhesion promoter according to claim 1, characterized in that: The preparation method of the modified filler is: (1) mixing carboxylated double-walled carbon nanotubes, carboxylated graphene oxide and carboxylated silicon dioxide in a mass ratio of 1: (1.2-1.5): (0.4-0.7) to obtain a filler, mixing 1 mass part of 3-isocyanate propyltrimethoxysilane and 0.12-0.15 mass parts of the filler under a nitrogen atmosphere, performing ultrasonic treatment for 20-25 minutes, adding 50-55 mass parts of N,N-dimethylformamide, stirring at 100-108° C. for 2-3 hours, centrifuging, and freeze-drying the obtained solid product A to obtain an isocyanate-modified filler; (2) 9-12 parts by weight of isocyanate-modified filler and 60-65 parts by weight of ethanol are mixed, and then an aqueous solution of carboxylated polystyrene microspheres is added dropwise, stirred at 55-60° C. for 2-3 hours, centrifuged, and the obtained solid product B is freeze-dried to obtain a modified filler.
5. The optical fiber coating adhesion promoter according to claim 4, characterized in that: The average particle size of the carboxylated polystyrene microspheres in the carboxylated polystyrene microsphere aqueous solution is 20 nm, and the solid content is 2.5 wt %.
6. The optical fiber coating adhesion promoter according to claim 5, characterized in that: The mass ratio of the isocyanate modified filler to the carboxylated polystyrene microspheres is 10:2-5.
7. The optical fiber coating adhesion promoter according to claim 1, characterized in that: The epoxy acrylate is selected from one or more of CN104NS, CN120NS, CN150NS, and CN2003NS.
8. The optical fiber coating adhesion promoter according to claim 7, characterized in that: The epoxy acrylate is a mixture of CN104NS, CN150NS and CN2003NS in a mass ratio of 1: (1.4-1.6): (0.2-0.5).
9. A method for preparing the optical fiber coating adhesion promoter according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: mixing propylene glycol methyl ether acetate, isobutyl alcohol and water, adding epoxy resin, modified filler and epoxy acrylate in sequence under stirring, adding phosphoric acid dropwise after stirring evenly, and continuing stirring for 2-3 hours to obtain the product.
10. An application of the optical fiber coating adhesion promoter according to any one of claims 1 to 8, characterized in that: Used to prepare optical fiber coatings made from acrylic resin formula systems.
Citation Information
Patent Citations
Optical fiber coating adhesion promoter and preparation method thereof
CN115340783A
Production of chloro-s-triazine triones and their use in cleansing or bleaching compositions
EP0000292A1
General adhesion promoter for paint and method of producing the same
CN101429356A
Double-component flexible epoxy structural adhesive and preparation method thereof
CN104403617A
Intrinsic flame-retardant cable head flash-sealing coating and preparation method thereof
CN111171704A
Cited By
Preparation method of anti-ultraviolet weather-resistant water-based paint
CN120536034A